Facebook Beacon : cool feature or an invasion of privacy? (A) - Borchers, William R.; Lilley, Brett W.; ORourke, James S. (London : SAGE Publications Ltd, 2017)
In November 2007, Facebook introduced Beacon, a feature designed to share a users online activities with friends. With concerns for their privacy, outraged Facebook users began expressing their negative feelings about Beacon. The feature soon become a privacy nightmare for the public, instead of the beneficial addition Facebook envisioned it to be. Now the company is left wondering how to handle its mistakes while maintaining a delicate balance between revenue growth and user privacy.
Originally published: Borchers, W. R., Lilley, B. W., & ORourke, J. S. (2008). Facebook Beacon: Cool feature or an invasion of privacy? (A). 08-07 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Facebook (Firm); Social media -- Economic aspects; Privacy, Right of